Cognição sociedade e o novo autoritarismo uma análise de algumas abordagens científicas e suas conseqüências éticas - Humberto Mariotti (EccoS – Revista Científica)
When applied to daily practice, scientific theories inevitably lead to ethical consequences that are rarely mentioned. Nowadays, when the majority of countries in the world seem to be free of authoritarian governments, it is important to pay attention to a new and active form of authoritarianism. It comes from the hypothesis that the world is the same for everybody, and therefore must be perceived like that. This hypothesis works as the basis of the standardization of collective mind by well-defined worldwide marketing strategies. Their scientific basis can be traced to theories such as the computationalist and the connexionist models of cognitive science. There is, however, a third approach the enactive model of cognitive science , that proposes that the world in which we live is constructed by ourselves along with our interactions with it, in the very flow of the living process. When lead to practice, this approach has the potential to produce ethical consequences opposed to those seen in the case of the two aforementioned approaches to cognitive science.